Comparison of the Angulation of the Unerupted Mandibular Second Premolar in Turkish Population with Tooth Agenesis - Samed Şatır; Muhammed Hilmi Büyükçavuş (Galenos Yayinevi, 2019)
Objective:This study aimed to evaluate the unerupted mandibular second premolar (MnP2) angulation in individuals with different tooth agenesis in Turkish population.Methods:We retrospectively reviewed panoramic radiographs of patients treated at Akdeniz University. According to the agenesis, the subjects were categorized into three groups: 22 patients with unilateral MnP2 agenesis (Group 1), 22 patients with bilateral mandibular incisor agenesis (MnI, Group 2), and 22 patients with no agenesis excluding third molars (Group 3). The angle between the first mandibular molar and unerupted MnP2 (ɣ angle) and the angle between the mandibular basis and unerupted MnP2 (Ɵ angle) were measured on both the right and left sides in Groups 2 and 3 using the method determined by Shalish et al.Results:Groups 1 and 2 were compared with the control group with respect to (ɣ) and (Ɵ). No significant difference was found between Groups 2 and 3 on both the right and left sides (p>0.05). The comparison between Groups 1 and 3 revealed significant differences in the ɣ and Ɵ angle only on the left side (p>0.05).Conclusion:Posterior rotation of the mandibular condyle during the growth-development period may be one of the factors responsible for the difference in the Ɵ angle between the MnI agenesis and control groups. A difference in the total number of teeth on the dental arch may be a reason for the differences in the ɣ angle between the MnI agenesis and control groups.